Defining the Phosphodiesterase Superfamily Members in Rat Brain Microvessels - He, Zhen (American Chemical Society, 2011)
[Image: see text] Eleven phosphodiesterase (PDE) families are known, each having several different isoforms and splice variants. Recent evidence indicates that expression of individual PDE family members is tissue-specific. Little is known concerning detailed PDE component expression in brain microvessels where the blood-brain-barrier and the local cerebral blood flow are thought to be regulated by PDEs. The present study attempted to identify PDE family members that are expressed in brain microvessels. Adult male F344 rats were sacrificed and blocks of the cerebral cortex and infratentorial areas were dissected. Microvessels were isolated using a filtration method, and total RNA was extracted. RNA quality and quantity were determined using an Agilent bioanalyzer. The isolated cortical and infratentorial microvessel total RNA amounts were 2720 ± 750 ng (n = 2) and 250 ± 40 ng (n = 2), respectively. Microarrays with 22 000 transcripts demonstrated that there were 16 PDE transcripts in the PDE superfamily, exhibiting quantifiable density in the microvessels. An additional immunofluorescent study verified that PDE4D (cAMP-specific) and PDE5A (cGMP-specific) were colocalized with RECA-1 (an endothelial marker) in the cerebral cortex using both F344 rats and Sprague–Dawley rats (n = 3–6/strain). In addition, PDE4D and PDE5A were found to be colocalized with alpha-smooth muscle actin which delineates cerebral arteries and arterioles as well as pericytes. In conclusion, a filtration method followed by microarray analyses allows PDE components to be identified in brain microvessels, and confirmed that PDE4D and PDE5A are the primary forms expressed in rat brain microvessels.